Targeting Tumor Vascular CD99 Inhibits Tumor Growth - Huijbers, Elisabeth J. M.; van der Werf, Inge M.; Faber, Lisette D.; Sialino, Lena D.; van der Laan, Pia; Holland, Hanna A.; Cimpean, Anca M.; Thijssen, Victor L. J. L.; van Beijnum, Judy R.; Griffioen, Arjan W. (Frontiers in Immunology, 2019)
CD99 (MIC2; single-chain type-1 glycoprotein) is a heavily O-glycosylated transmembrane protein (32 kDa) present on leukocytes and activated endothelium. Expression of CD99 on endothelium is important in lymphocyte diapedesis. CD99 is a diagnostic marker for Ewing’s Sarcoma (EWS), as it is highly expressed by these tumors. It has been reported that CD99 can affect the migration, invasion and metastasis of tumor cells. Our results show that CD99 is also highly expressed in the tumor vasculature of most solid tumors. Furthermore, we found that in vitro CD99 expression in cultured endothelial cells is induced by starvation. Targeting of murine CD99 by a conjugate vaccine, which induced antibodies against CD99 in mice, resulted in inhibition of tumor growth in both a tumor model with high CD99 (Os-P0109 osteosarcoma) and low CD99 (CT26 colon carcinoma) expression. We demonstrated that vaccination against CD99 is safe, since no toxicity was observed in mice with high antibody titers against CD99 in their sera during a period of almost 11 months. Targeting of CD99 in humans is more complicated due to the fact that the human and mouse CD99 protein are not identical. We are the first to show that growth factor activated endothelial cells express a distinct human CD99 isoform. We conclude that our observations provide an opportunity for specific targeting of CD99 isoforms in human tumor vasculature.